Variation in Length of Contact with Water and Frequency of Wash Hands on Dermatitis in Housewives - Asni Hasaini; Muhlisoh Muhlisoh; Martini Nur Sukmawaty (GLOBAL HEALTH SCIENCE GROUP, 2022)
The high incidence of dermatitis reaches 15-20% and the prevalence of contact dermatitis in Indonesia is 66.3%. Contact dermatitis due to contact with materials/tools used in each activity. One of the activities that are often in contact with water and washing hands is housewives. The purpose of this study was to analyze the effect of variations in the length of contact with water and hand washing on dermatitis in housewives in the Astambul District. The research is quantitative with an observational analytic design with a cross-sectional design. The sample in this study amounted to 100 respondents with purposive sampling. The instruments used are questionnaires and observations. Data analysis used multiple logistic regression tests. The results showed that 23% of housewives experienced dermatitis, the variation factor of contact with water (ρ value = 0.004), and hand washing times (ρ value = 0.000). And the multivariate results showed that the variation in the length of contact with water was the most influential factor in the incidence of dermatitis (OR = 0.181). In conclusion, the most influential variable on the incidence of dermatitis in housewives is the variation in the length of contact with water (> 2 hours).